Evaluation of Some Proposed Methods for Protecting Bridge Substructure Using Physical Models - Mohammed, Thamer Ahmed; Jafaar, Mohd Saleh; Thanoon, Waleed Abdulmalik; Ghazali, Abdul Halim; Megat Mohd Noor, Megat Johari; Yusuf, Badronnisa; Salem, Mohammed (Universiti Putra Malaysia Press, 2003)
Bridges constructed across streams with erodable beds are normally subjected to serious scouring during the flood at piers and abutment sites. As a result, scour holes will be formed at the bridge substructure. The scour hole can be described by its maximum vertical scour depth which is called local scour depth and by the size of its projected scour area. Experience has shown that progressive depth of scour holes at the site of bridge substructures could undermine the foundation and result in bridge failure. Protection against scouring for constructed bridges is necessary to minimize the risk of failure. The formation of the scour hole at the bridge substructure is considered as very complex and this phenomenon is so involved that only very limited success has been made to predict the size of the scour hole computationally. Physical model remains the principal tool employed for estimating the size of scour hole at the site of bridge substructure. In this study, the efficiency of five different proposed methods of protecting the bridge substructure were tested using a physical model. These methods are piers with collar, pier with multiple collars, pier with slot, piles in front of piers, and using riprap. The physical model comprises a tilted flume (5 m long, 76 mm wide and 250 mm high) with sand on its bed (nominal size =0.35 mm) and a single circular cylindrical pier model which was made of hard teak wood (diameter =16 mm). A collar form steel with a diameter of 40 mm was attached to the pier model. A slot of a dimension 7 mm x 20 mm (width x depth) was opened in the upper side of the pier. Steel nails 3 mm in diameter each were used to simulate the piles. Coarse graded gravel was used as a riprap. Data collected from the physical model showed that using multiple collars around the pier can give 88% reduction in the scour area while the reduction in the maximum scour depth ranges from 73% to 64%, depending on the flow rate in the flume. It was observed that the riprap protection at the bridge substructure is also effective in reducing the maximum scour depth and reduction ranges from 100% to 68%. However, the reduction in the scour area ranges from 100% to 83%. The reduction was also dependent on the flow rate.